U.S. Border Enforcement and Mexican Immigrant Location Choice - Sarah Bohn; Todd Pugatch (Institute for the Study of Labor (IZA), 2013)
We provide the first evidence on the causal effect of border enforcement on the full spatial distribution of Mexican immigrants to the United States. We address the endogeneity of border enforcement with an instrumental variables strategy based on administrative delays in budgetary allocations for border security. We find that 1,000 additional border patrol officers assigned to prevent unauthorized migrants from entering a state decreases that state's share of Mexican immigrants by 21.9%. Our estimates imply that border enforcement alone accounted for declines in the share of Mexican immigrants locating in California and Texas of 11 and 6 percentage points, respectively, over the period 1994-2011, with all other states experiencing gains or no change.
Keywords: J15; J61; 330; unauthorized immigration; border enforcement; Mexico; residential location choice